Exploring Trust and Perceived Risk in Digital Payment Adoption among MSMEs: A Phenomenological Approach - Weku, Christoffel E.F.; Aldrin, Andi Indah Deliyanti; Ridha, Achmad (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Digital payment systems have expanded rapidly in Indonesia, offering micro, small, and medium enterprises (MSMEs) opportunities to improve transaction efficiency and strengthen financial inclusion. However, adoption among MSMEs remains uneven, suggesting that technological benefits alone do not fully explain acceptance. This study explores how MSME owners in Makassar experience trust and perceived risk in adopting digital payment systems. Using a qualitative phenomenological approach, data were collected through in-depth semi-structured interviews with twelve MSME owners operating across diverse sectors in Makassar. The interviews were transcribed verbatim and analyzed manually through iterative data reduction, coding, and thematic development to capture the essence of participants’ lived experiences. The findings reveal four interconnected themes. First, trust emerged as an experiential outcome shaped by repeated successful transactions and perceived system reliability. Second, perceived risk persisted as an emotional concern, particularly related to financial loss and loss of control during transaction uncertainty. Third, trust and risk were actively negotiated through social validation from peer MSMEs and institutional cues such as regulatory legitimacy. Fourth, trust and perceived risk jointly shaped adoption as an adaptive process, leading to selective and hybrid usage patterns rather than full replacement of cash transactions. This study contributes to digital payment adoption literature by reframing trust and perceived risk as lived, dynamic experiences embedded in everyday business practices. Practically, the findings highlight the need for payment providers and policymakers to strengthen system reliability, improve transparent dispute-handling mechanisms, and leverage community-based trust-building strategies to support sustainable digital payment adoption among MSMEs.